Isolation and synthesis of two hydroxychavicol heterodimers from Piper nudibaccatum. Issue 16 (22nd April 2015) - Liu, Hong-Xin; Tan, Hai-Bo; He, Meng-Ting; Li, Ling; Wang, Yue-Hu; Long, Chun-Lin
Abstract: Two hydroxychavicol heterodimers comprising phenylpropanoid and monoterpene constituent units, named nudibaccatumins A (1 ) and B (2 ), were isolated as an inseparable mixture from the aerial parts of Piper nudibaccatum . Their absolute configurations were confirmed by total synthesis using ortho -alkylation of hydroxychavicol with myrtenyl bromide as the key reaction. The two new compounds (1 and2 ) and their synthetic analogues (3 –8 ) were evaluated for XO inhibitory activity. Graphical abstract: